Reciprocity and voting - Volker Hahn (University of Heidelberg, Department of Economics, 2004)
In this paper we present a two-period model where a left-wing and a right-wing political party are solely interested in the politics they pursue. We assume that voters are fully rational but show reciprocal behavior. By contrast, political parties are not motivated by reciprocity. We show that reciprocity may have dramatic consequences for models of voting behavior. The incentive to be kind to the median voter may guarantee that a position closer to the the median voter's position is adopted even when political parties are not directly interested in being elected and cannot commit to a political stance during an election campaign. Moreover, reciprocity increases incumbency advantages.
Keywords: D72; 330; Reciprocity; Voting; Median Voter Theorem; Wahlverhalten; Gerechtigkeit; Medianwähler-Modell; Theorie